CHARLES HADDON SPURGEON: WHAT CAN WE LEARN FROM HIM FOR TODAY? - Andrew McGowan (STTRII, 2019)
In this article, the author gives an account of the life and theology of C.H. Spurgeon (1834-1892), the famous Reformed Baptist Minister, who preached in London in the second half of the nineteenth century. The account demonstrates that Spurgeon was not only the most renowned preacher of his day, most of whose sermons were published and are still read widely today but also an author who published many volumes. In addition to his work as preacher and writer, Spurgeon built children’s orphanages, started a theological college and assisted in many noble causes. As part of this benevolent work, his church contributed large sums to support poor relief. Having told Spurgeon’s story, the article then indicates six areas of Spurgeon’s life and ministry which are helpful for us today: his Passion for Souls; his Devotion to Prayer and Study; His attitude to the Bible & Expository Ministry; his Pastoral Ministry; His Practical Christianity; and His refusal to compromise on the truth of the gospel. KEYWORDS: Spurgeon, ministry, preach, Bible